2017
DOI: 10.1002/chem.201703602
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox Catalysis with Metal Complexes Made from Earth‐Abundant Elements

Abstract: Photoredox chemistry with metal complexes as sensitizers and catalysts frequently relies on precious elements such as ruthenium or iridium. Over the past 5 years, important progress towards the use of complexes made from earth-abundant elements in photoredox catalysis has been made. This review summarizes the advances made with photoactive Cr , Fe , Cu , Zn , Zr , Mo , and U complexes in the context of synthetic organic photoredox chemistry using visible light as an energy input. Mechanistic considerations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
253
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(275 citation statements)
references
References 134 publications
6
253
0
Order By: Relevance
“…[1,2] Except for copper(I) complexes, [2] strongly luminescent molecular complexes of earth-abundant-metal ions were essentially unknown until very recently.N ear-IR (NIR) emission with mononuclear copper(I) complexes is still very rare. It is motivated by the desire to replace expensive noble-metal ions and rare-earth-metal ions by earth-abundant metal ions in the fields of photosensitizing, photoluminescence,a nd photoredox reactions.…”
mentioning
confidence: 99%
“…[1,2] Except for copper(I) complexes, [2] strongly luminescent molecular complexes of earth-abundant-metal ions were essentially unknown until very recently.N ear-IR (NIR) emission with mononuclear copper(I) complexes is still very rare. It is motivated by the desire to replace expensive noble-metal ions and rare-earth-metal ions by earth-abundant metal ions in the fields of photosensitizing, photoluminescence,a nd photoredox reactions.…”
mentioning
confidence: 99%
“…Theemission maxima and t PL values of 1 and 2 in doped films at 77 Kwere found to be similar to those at RT (Supporting Information, Table S12). [3] Compounds 1 and 2 possess significantly higher E Red *values compared to those of benchmark photocatalysts such as [Ru(bpy) 3 ] 2+ (E Red * = 0.77 V), [2] [Ir(dF(CF 3 )ppy) 2 (dtbubpy)] + (where dF-(CF 3 )ppy = 2-(2,4-difluorophenyl)-5-(trifluoromethyl)pyridinato-C 2 ,N'), (E Red * = 0.89 V), [21] [Cr(Ph 2 phen) 3 ] 3+ (where Ph 2 phen = 4,7-diphenyl-1,10-phenanthroline) (E Red * = 1.40 V) 2 ,t riphenylpyrylium (E Red * = 2.30 V) [22] and mesityl diaminoacridinium (E Red * = 1.25 V) [23] thus making 1 and 2 amongst the strongest photo-oxidants identified to date (Supporting Information, Table S13). SCE, for 1 and 2,respectively (Supporting Information, Table S13).…”
mentioning
confidence: 99%
“…Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands. [2] Much less explored as as trategy is the harnessing of LMCT states using electronpoor metals with electron-rich ligands. [2] Much less explored as as trategy is the harnessing of LMCT states using electronpoor metals with electron-rich ligands.…”
mentioning
confidence: 99%
“…[Ru(bpy) 3 ] 2+ , [Ir(ppy) 3 ] etc.) which possess these properties and examples of photo redox catalysts based on first‐row transition metals are extremely scarce . Twigging the requirement for economically viable, more abundant first row transition metal photoactive catalysts, we explored the use of macrocyclic meso ‐tetraphenylporphyrin ligand coordinated Ni(II) complex [NiTPP] as a photoredox catalyst and disclosed its dual excited state redox properties, i. e., oxidative quenching as well as reductive quenching representing two different sets of chemical reactions under visible light promoted condition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%